Beta-glucan-rich extract from pleurotus sajor-caju (Fr.) singer prevents obesity and oxidative stress in C57BL/6J Mice fed on a high-fat diet - Kanagasabapathy, G.; Malek, S.N.A.; Mahmood, A.A.; Chua, Kek Heng; Vikineswary, S.; Kuppusamy, Umah Rani (Hindawi, 2013)
Mushrooms have been used in folk medicine for thousands of years. In this study, the effect of beta-glucan-rich extract of P. sajor-caju (GE) on lipid lowering and antioxidant potential was assessed in C57BL/6J mice fed on a high-fat diet. Obesity was induced in C57BL/6J mice by feeding a high-fat diet. The control groups in this study were ND (for normal diet) and HFD (for high-fat diet). The treated groups were ND 240 (for normal diet) (240 mg/kg b.w) and HFD60, HFD120, and HFD240 (for high-fat diet), where the mice were administrated with three dosages of GE (60, 120, and 240 mg GE/kg b.w). Metformin (2 mg/kg b.w) served as positive control. GE-treated groups showed significantly reduced body weight, serum lipid, and liver enzymes levels. GE also attenuated protein carbonyl and lipid hydroperoxide levels by increasing the enzymic antioxidants (SOD, CAT, and GPx) activities in the mice. GE-treated groups induced the expression of hormone sensitive lipase (HSL) and adipose triglyceride lipase (ATGL) while downregulated the expression of peroxisome proliferator-activated receptor gamma (PPAR-gamma), sterol regulatory binding protein-1c (SREBP-1c), and lipoprotein lipase (LPL). Hence, GE prevented weight gain in the mice by inducing lipolysis and may be valuable in the formulation of adjuvant therapy for obesity.